Social Learning and Solar Photovoltaic Adoption - Kenneth Gillingham; Bryan Bollinger (Center for Economic Studies and Ifo Institute (CESifo), 2020)
A growing literature points to the effectiveness of leveraging social interactions and nudges to spur adoption of pro-social behaviors. This study investigates a large-scale behavioral intervention designed to actively leverage social learning and peer interactions to encourage adoption of residential solar photovoltaic systems. Municipalities choose a solar installer offering group pricing, and undertake an informational campaign driven by volunteer ambassadors. We find a causal treatment effect of 37 installations per municipality from the campaigns, and no evidence of harvesting or persistence. The intervention also lowers installation prices. Randomized controlled trials based on the intervention show that selection into the program is important while group pricing is not. Our results suggest that the program provided economies of scale and lowered consumer acquisition costs, leading to low-cost emissions reductions.
Keywords: D03; L22; Q42; Q48; 330; non-price interventions; social learning; renewable energy; solar photovoltaic panels; technology adoption; natural experiment